2007
DOI: 10.1128/jvi.02629-06
|View full text |Cite
|
Sign up to set email alerts
|

The Adenovirus E4 ORF3 Protein Binds and Reorganizes the TRIM Family Member Transcriptional Intermediary Factor 1 Alpha

Abstract: One of the most interesting functions attributed to the adenovirus early region 4 open reading frame 3 (E4 ORF3) protein is its reorganization of promyelocytic leukemia (PML) protein nuclear bodies. These normally punctate structures are reorganized by E4 ORF3 into tracks that eventually surround viral replication centers. PML rearrangement is an evolutionarily conserved function of E4 ORF3, yet its cause and functional relevance remain mysteries. The E4 ORF3 protein coimmunoprecipitates with the PML protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…It has long been established that early during infection E4orf3 reorganizes PML nuclear bodies to form distinct nuclear track-like structures that contain the cellular proteins PML, SP-100, the MRN complex, and TIF1␣ (19,25,65,78). Of these, only the MRN component, MRE11, is subsequently targeted to cytoplasmic aggresomes for E1B-55K/E4orf6-dependent degradation (2,30,44).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has long been established that early during infection E4orf3 reorganizes PML nuclear bodies to form distinct nuclear track-like structures that contain the cellular proteins PML, SP-100, the MRN complex, and TIF1␣ (19,25,65,78). Of these, only the MRN component, MRE11, is subsequently targeted to cytoplasmic aggresomes for E1B-55K/E4orf6-dependent degradation (2,30,44).…”
Section: Discussionmentioning
confidence: 99%
“…2A). Since it has previously been established that the TIF1 family member, TIF1␣ is reorganized by E4orf3 to PML-containing nuclear tracks in Adinfected cells (78) we next assessed whether TIF1␥ colocalizes with E4orf3 and PML in Ad-infected cells. Consistent with the notion that TIF1␥ might be recruited along with TIF1␣ to PMLcontaining nuclear tracks, these analyses revealed that TIF1␥ colocalized with PML in both Ad5-and Ad12-infected cells (Fig.…”
Section: Tif1␥ Is Reorganized To Pml-containing Nuclear Tracks Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, PML, Sp100, Daxx, SUMO-1, and TIF1␣ are relocated into these tracks by E4orf3 (163)(164)(165)(166), which might resemble nuclear aggresomes (167). These PML-containing structures are thereafter localized adjacent to viral RCs.…”
Section: Nuclear Dna Virus Replication Centersmentioning
confidence: 99%